Mastering the pedagogical potential of cultural and educational city environment: The experience of implementing project-based master's degree programme - Larisa I. Cheremisinova; Tatyana G. Firsova (Saratov State University, 2021)
The purpose of the study is to present the methodological fundamentals of the development of cultural and educational environment of the city within primary education. We proved the necessity of revising training techniques for teaching culture under conditions of higher education. We explained top priority of orientation towards humanitarian, anthropological and axiological approaches to organization of mastering local lore at school and university. The cultural and educational environment of the city, i.e. the place, where a person was born, is considered as a tool for the interiorization of universal human values. The study gave reasons for importance of involving children in local lore activities at primary school age. Local lore is considered as a scientific basis for designing the content of school subjects; as a cultural training, activity aimed at learning about the heritage of one's native city, preserving and enhancing the cultural level of the region, its inner potential; as a social activity aimed at developing civic mindedness. The article determined the possibilities of using local lore to teach moral and spiritual values to primary schoolchildren. The study described experience of creating and implementing a project-based research-based master's degree programme at Saratov State University, aimed at training primary school teachers to use local lore materials in the educational process at school. The article reveals the structural and content components of the educational programme, the main forms and teaching methods. The article outlines the topics for student projects in the field of literary, linguistic, mathematical, and ecological local lore. We presented various methodological forms of incorporating local material in the class and extracurricular activities of younger students: compilation of interactive educational resources (books, reference books, albums, presentations, didactic problem books), preparation of quest games, virtual excursions, subject and intersubject projects. The article gives examples of cross-curricular competitions, mathematical problems with regional content. The priority area is the immersion of students (both students and schoolchildren) in the cultural environment of the city, region.